2016
DOI: 10.1242/jeb.124495
|View full text |Cite
|
Sign up to set email alerts
|

Muscle memory and a new cellular model for muscle atrophy and hypertrophy

Abstract: Memory is a process in which information is encoded, stored, and retrieved. For vertebrates, the modern view has been that it occurs only in the brain. This review describes a cellular memory in skeletal muscle in which hypertrophy is 'remembered' such that a fibre that has previously been large, but subsequently lost its mass, can regain mass faster than naive fibres. A new cell biological model based on the literature, with the most reliable methods for identifying myonuclei, can explain this phenomenon. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 119 publications
9
132
0
5
Order By: Relevance
“…The relevant bottleneck relating the number of nuclei to cytoplasmic volume is not known, although it has been speculated that capacity for shuttling of macromolecules over the nuclear membrane could act as a limiting factor if the number of nuclei is not sufficiently high (Gundersen, 2016;Hall et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant bottleneck relating the number of nuclei to cytoplasmic volume is not known, although it has been speculated that capacity for shuttling of macromolecules over the nuclear membrane could act as a limiting factor if the number of nuclei is not sufficiently high (Gundersen, 2016;Hall et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of the muscle memory phenomenon Bruusgaard et al, 2010;Egner et al, 2013; for a review, see Gundersen, 2016), for which efficient re-growth relies on myonuclei recruited during a previous hypertrophic episode, is an important example of functional radial growth without the need for new myonuclei from satellite cells. This has been directly demonstrated using the hind limb suspension model, in which atrophy is induced by lifting up the hind part of rodents by the tail and thereby unloading the hind leg.…”
Section: Is Recruitment Of Scs Obligatory For Hypertrophy?mentioning
confidence: 99%
“…However, apoptosis as a mechanism for causing myonuclear loss during muscle atrophy is highly controversial, as recent studies using in vivo time-lapse imaging found that the number of myonuclei remained relatively constant during both tenotomy (see Glossary) and detraining (Gundersen, 2016). Whereas in vivo imaging allows direct examination of myonuclei, many studies have reported markers for apoptosis in homogenates derived from atrophying muscle and have interpreted this as apoptosis of myonuclei, but these findings could reflect apoptosis of nuclei from other cell types, such as stromal cells or satellite cells (Gundersen, 2016).…”
Section: Mafbx Murf1mentioning
confidence: 99%
“…Whereas in vivo imaging allows direct examination of myonuclei, many studies have reported markers for apoptosis in homogenates derived from atrophying muscle and have interpreted this as apoptosis of myonuclei, but these findings could reflect apoptosis of nuclei from other cell types, such as stromal cells or satellite cells (Gundersen, 2016). Indeed, a recent study found that although the amount of Bax mRNA and the number of TUNEL-positive nuclei were significantly increased in immobilised human muscle, this was mainly localised in the interstitial space between myocytes, thus potentially being attributable to other cell types (Suetta et al, 2012).…”
Section: Mafbx Murf1mentioning
confidence: 99%
“…The plastic nature of muscle, and its syncytial status, has given rise to a controversy in the field that only recently appears to have been resolved-the "myonuclear domain hypothesis" [7][8][9]. This theory has its origins in the concept of "Wirkungssphäre, " or "sphere of influence," proposed by Strassburger in 1893 [10], in which he argued that a nucleus can only support a descrete volume of cytoplasm, which in turn defines the upper limits to cell size.…”
Section: Commentarymentioning
confidence: 99%